Radial variability of quantitative features of tracheids in Pinus caribaea var. hondurensis from 25 years old plantations - Márquez-Carrero, Gabrialy (2022)
This research is about variability of quantitative features (length, diameter, thickness, wall fraction) in tracheids of Pinus caribaea var. hondurensis from 25 years old plantations from Uverito (Monagas state, Venezuela). Six trees were studied and macerated tissue were prepared in three positions in cross section: near of pith, middle point of cross section and near of cambium. Higher diameter was observed in early wood and in late wood were found higher thickness wall. Tracheid length had an increment from the pith to middle point and, then, showed a reduction from middle point to cambium. According variation in tracheids length, adult wood appears from the middle point to cambium.